Perspectives of La0.9Sr0.1Fe0.9Co0.1O3±δ perovskite obtained by Pechini and sonochemical methods: a case study - Gloria E. de la Huerta-Hernández; Tatiana Rodríguez-Flores; Armando Reyes-Montero; Iván Castro-Cisneros; Isaías Hernández-Pérez; José A. Chávez-Carvayar (Royal Society Open Science, 2024)
The sonochemical method is a novel synthesis route that takes advantage of the use of ultrasonic radiation to obtain different nanomaterials with an improvement in the process variables and material characteristics. In this work, two different synthesis routes to obtain a double perovskite structure were compared in detail. The Pechini synthesis method is a widely used and effective way to obtain this kind of structure by the formation of a cross-linked network of metal cations. Alternatively, in sonochemistry, chemical reactions occur with the application of powerful ultrasound radiation. The final characteristics of synthesized powders of La0.9Sr0.1Fe0.9Co0.1O3±δ (LSFC) were analysed thermally, structurally, morphologically and optically, and their transport properties were evaluated to determine their semiconductor character in a solid oxide fuel cell device and in photocatalytic processes. Structural results indicated a well crystallized perovskite structure with a single cubic phase. The cell parameter a (approx. 3.89 Å) and crystal size measurements (11–20 nm) were determined by Rietveld refinement for samples obtained by both synthesis methods. Thescanning electron microscope micrographs showed aggregates with homogeneous morphology and a uniform particle size distribution, with a rough and porous surface. Optical properties were determined by ultraviolet–visible spectrophotometry and photoluminescence, resulting in an Eg of 1.2 and 0.8 eV in samples from Pechini and sonochemistry, respectively.